Research made real : a guide for students - Walsh, Mark. (Cheltenham : Nelson Thornes, 2001)
This text is designed to help students with social science research projects. It contains a balance of theory and practice materials, learning support and activity features, and short case study materials.
Includes bibliographical references (p. 107-108) and index.
Keywords: Social sciences -- Research; Social sciences -- Methodology; Society